HERBAL POTENSIAL SEBAGAI HAND SANITAIZER DI INDONESIA : LITERATUR REVIEW - Thalib, abdul (Pasapua Health Journal, 2020)
Introduction : Covid 19 pandemic that befell the world today makes the need for clean and healthy life behavior increase. The necessity to wash hands is often hampered, especially when on the road so hand sanitizers are an alternative to hand washing. Hand sanitizers with natural ingredients tend to be more friendly to the skin. Method : Literature review is carried out on the Garuda and Google Scholar data base. Articles are restricted from 2015- 2019. With keywords natural ingredients, herbs, hand sanitizers, antibacterial, antifungal, and antiviral. Result: Based on literature search on 2 data based found 86 studies related to each Garuda: 28 articles, Google Scholar: 58 articles. After screening the title and abstract, 57 articles and 2 double articles were then issued so that 27 articles were reviewed in full. Of these there are 13 articles that identify the use of herbal ingredients used as hand sanitizers and have the ability to be antibacterial, antiviral and antifungal. Conclusion :The use of herbs as a hand sanitizer is very potential to be used, however it is still necessary to pay attention to the standards of making hand sanitizers, namely viscosity, PH, homogeneity and inhibition. Some active compounds that function as antibacterial agents such as auron flavonoids, quercetin, limonene, larchein